Efektifitas Model Pembelajaran Outdoor Study Berbantu Media Audiovisual untuk Meningkatkan Hasil dan Minat Belajar Siswa - Andriani, Syamsiyatul; Ardianti, Sekar Dwi; Masfuah, Siti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The study's objectives were to compare the outcomes of students' science learning prior to and following the use of audiovisual media and to investigate the effect of the Outdoor Study model on students' interest in learning. The Pre-Experimental Design with the One-Group Pretest-Posttest Design model is this quantitative experimental research design. Using a student learning interest questionnaire, the written test method generates objective data in the form of multiple choice and non-test data. Class IV SDN Tanjunganom 01 will serve as the setting for this investigation. The saturated sample method was used to collect samples from all twenty fourth-grade students in this study. In accordance with the findings of this study, the Paired Sample T-Test hypothesis test score with a Stg.(2-tailed) value of 0.000 0.05 indicates that the Outdoor Study model is supported by the influence of audiovisual media on class student interests. To pursue a career in science, IV SDN Tanjunganom 01 received an average score of 73 on the post-test and 55 on the pre-test.The N-Gain test, on the other hand, had an average value of 0.58, indicating a moderate increase in the criteria for improving student learning outcomes following treatment. The percentage of N-Gain scores is 58%, indicating that the interpretation of the effectiveness of the Outdoor Study learning model supported by audiovisual media can be categorized as quite effective in increasing students' understanding of science concepts.